HUBUNGAN STATUS GIZI DENGAN SIKLUS MENSTRUASI PADA REMAJA PUTRI DI PSIK FK UNSRAT MANADO - Felicia, Felicia; Hutagaol, Esther; Kundre, Rina (JURNAL KEPERAWATAN, 2015)
Abstract: Adolescence is a time of transition from childhood to adulthood is marked a change in the physical, psychological and psychosocial. In girls, puberty is marked by the onset of menstruation (menarche). In adolescent girls needed a good nutritional status in helping the growth of adolescents including menstrual cycle regularity. Young women who have less or more nutritional intake can cause reproductive dysfunction and impact on menstrual disorders. The aim of research to determine the relationship of nutritional status with menstrual cycle in young women at PSIK FK UNSRAT Manado. Design research is an analytic survey with cross sectional, population that all young women who met the inclusion criteria. This research sample 67 respondents obtained by using purposive sampling technique. The instrument using questionnaire menstrual cycle and observation sheet measurement results of weight and height were performed. The results of the statistical test using Chi Square test at 95% significance level (Î± â‰¤ 0.05), then the p value = 0.000. This means that the value of p <Î± (0.05). Thus that there is a significant relationship between nutritional status and the menstrual cycle in young girls at PSIK FK UNSRAT Manado. Advice for young women to better maintain nutritional status and maintain their reproductive health so that they become a regular menstrual cycle. Keywords: Nutritional status, menstrual cycles, young women. Abstrak: Masa remaja merupakan masa transisi atau peralihan dari masa anak-anak menuju dewasa yang ditandai adanya perubahan fisik, psikis dan psikososial. Pada remaja putri, pubertas ditandai dengan permulaan menstruasi (menarche). Pada remaja putri dibutuhkan status gizi yang baik dalam membantu pertumbuhan remaja termasuk keteraturan siklus menstruasi. Remaja putri yang mengalami asupan gizi kurang atau lebih dapat menyebabkan gangguan fungsi reproduksi dan berdampak pada gangguan menstruasi. Tujuan penelitian untuk mengetahui hubungan status gizi dengan siklus menstruasi pada remaja putri di PSIK FK UNSRAT Manado. Desain penelitian yaitu survei analitik dengan rancangan cross sectional, populasi yaitu semua remaja putri yang memenuhi kriteria inklusi. Sampel penelitian ini 67 responden yang didapat dengan menggunakan teknik purposive sampling. Instrumen yang digunakan yaitu kuesioner siklus menstruasi dan lembar obeservasi hasil pengukuran berat badan dan tinggi badan yang dilakukan. Hasil uji statistik menggunakan uji Chi Square pada tingkat kemaknaan 95% (Î± â‰¤ 0,05), maka didapatkan nilai p = 0,000. Ini berarti bahwa nilai p < Î± (0,05). Dengan demikian bahwa terdapat hubungan yang bermakna antara status gizi dengan siklus menstruasi pada remaja putri di PSIK FK UNSRAT Manado. Saran untuk remaja putri agar lebih menjaga status gizi dan memelihara kesehatan reproduksi mereka agar siklus menstruasi mereka menjadi teratur. Kata kunci: Status Gizi, Siklus Menstruasi, Remaja Putri.